Foot and ankle problems in dancers - Kadel, N. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
The dancer`s foot and ankle are subjected to high forces and unusual stresses in training and performance. Injuries are common in dancers, and the foot and ankle are particularly vulnerable. Ankle sprains, ankle impingement syndromes, flexor hallucis longus tendonitis, cuboid subluxation, stress fractures, midfoot injuries, heel pain, and first metatarsophalangeal joint problems including hallux valgus, hallux rigidus, and sesamoid injuries will be reviewed. This article will discuss these common foot and ankle problems in dancers and give typical clinical presentation and diagnostic and treatment recommendations.